2007
DOI: 10.1093/jac/dkm230
|View full text |Cite
|
Sign up to set email alerts
|

Factors impacting the expression of membrane-bound proteins in lymphocytes from HIV-positive subjects

Abstract: Background: The cellular transport proteins ABCB1, ABCC1 and ABCG2 have been implicated in the efflux of some antiretroviral drugs, thus decreasing their intracellular concentrations. Decreased drug accumulation in lymphocytes may allow viral replication and the subsequent emergence of viral resistance leading to treatment failure. Expression of HIV co-receptors on the surface of lymphocytes may influence viral tropism and therefore viral pathogenicity and disease progression. Here, we describe the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
3
17
1
Order By: Relevance
“…A study reported that the expression of ABCB1 gene in lymphocytes extracted from HIV-positive patients was significantly greater in males relative to females, using GAPDH as an endogenous control with a male to female expression ratio of 1.34-fold (Chandler et al, 2007). However, the present findings suggest that GAPDH should not be used as a singleendogenous control for normalization of ABCB1 gene expression in PBMCs.…”
Section: Evaluation Of Housekeeping Gene Stabilitycontrasting
confidence: 67%
See 1 more Smart Citation
“…A study reported that the expression of ABCB1 gene in lymphocytes extracted from HIV-positive patients was significantly greater in males relative to females, using GAPDH as an endogenous control with a male to female expression ratio of 1.34-fold (Chandler et al, 2007). However, the present findings suggest that GAPDH should not be used as a singleendogenous control for normalization of ABCB1 gene expression in PBMCs.…”
Section: Evaluation Of Housekeeping Gene Stabilitycontrasting
confidence: 67%
“…Recently, it was found that P-gp expression in intestine and liver does not correlate with its expression in PBMCs (Albermann et al, 2005). A study reported that males have greater expression levels of ABCB1 in peripheral lymphocytes compared with females, approximately 1.3-fold, using glyceraldehyde-3P dehydrogenase (GAPDH) as an endogenous control gene for normalization (Chandler et al, 2007). However, another study concluded that beta-2 microglobulin (β-2M) is a more stably expressed endogenous control gene and should be used for normalization of the expression levels in lymphocytes, rather than GAPDH or beta-actin (actin-β), and that more than one gene should be used for normalization (Vandesompele et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that P-glycoprotein expression in human liver [32] and lymphocytes [33] was lower in females than in males, possibly due to the effects of estradiol and progesterone on P-glycoprotein expression [13]. Therefore, these sex hormones may contribute to the sex specificity in the effect of the MDR1 polymorphism on interpersonal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression in the endothelium of the blood-brain barrier prevents the entry of possibly toxic compounds into the brain [14,17]. Besides its expression in barrier tissues, P-glycoprotein is expressed in single cells such as lymphocytes, hematopoietic stem cells and cancer cells, thereby contributing in part to drug resistance in leukaemia and other tumours [18,19] and in HIV [20].…”
Section: Abcb1 Expressionmentioning
confidence: 99%